COVID-19 PANDEMIC AND DISTANCE LEARNING - HASIĆ, AMOR (Innovare Journal of Social Sciences, 2022)
The COVID-19 pandemic is for the first time in 2020 in Wuhan Province, China. It later spread to other countries in the world. In early April, the school in 194 countries, from pre-school to higher education, is closed. Approximately 1.5 billion students are affected by this situation, and therefore their status as full-time students have ceased. All countries with the COVID-19 pandemic aimed to provide continuing education without break. Traditional educational techniques are significantly disrupted by social alienation and restriction policies. Many scientists have shared their work on teaching and learning in different ways after the outbreak of COVID-19. There is face-to-face teaching abolished in many schools, colleges, and universities. Our state of Montenegro, following the example other countries in the world, introduced distance learning. The purpose of this research is to: (1) Application of learning and teaching activities with the help of communication technologies in mathematics teaching. (2) Determine the efficiency of distance learning mathematics. (3) Students’ reaction and observation before and after the application of distance learning. (4) Support and implementation of recommendations by the Ministry of Education.